Potential Application of T-Follicular Regulatory Cell Therapy in Transplantation - Dudreuilh, Caroline; Basu, Sumoyee; Scottà, Cristiano; Dorling, Anthony; Lombardi, Giovanna (Frontiers in Immunology, 2021)
Regulatory T cells (Tregs) constitute a small proportion of circulating CD4+ T cells that function to maintain homeostasis and prevent autoimmunity. In light of their powerful immunosuppressive and tolerance-promoting properties, Tregs have become an interesting potential candidate for therapeutic use in conditions such as solid organ transplant or to treat autoimmune and inflammatory conditions. Clinical studies have demonstrated the safety of polyclonally expanded Tregs in graft-versus-host disease, type 1 diabetes and more recently in renal and liver transplantation. However, Tregs are heterogenous. Recent insights indicate that only a small proportion of Tregs, called T follicular regulatory cells (Tfr) regulate interactions between B cells and T follicular helper (Tfh) cells within the germinal centre. Tfr have been mainly described in mouse models due to the challenges of sampling secondary lymphoid organs in humans. However, emerging human studies, characterise Tfr as being CD4+CD25+FOXP3+CXCR5+ cells with different levels of PD-1 and ICOS expression depending on their localisation, in the blood or the germinal centre. The exact role they play in transplantation remains to be elucidated. However, given the potential ability of these cells to modulate antibody responses to allo-antigens, there is great interest in exploring translational applications in situations where B cell responses need to be regulated. Here we review the current knowledge of Tfr and the role they play focusing on human diseases and transplantation. We also discuss the potential future applications of Tfr therapy in transplantation and examine the evidence for a role of Tfr in antibody production, acute and chronic rejection and tertiary lymphoid organs. Furthermore, the potential impact of immunosuppression on Tfr will be explored. Based on preclinical research, we will analyse the rationale of Tfr therapy in solid organ transplantation and summarise the different challenges to be overcome before Tfr therapy can be implemented into clinical practice.